Novel Computer-Aided Design-Based Collaboration Framework for the Conceptual–Embodiment Design Phase - Fariz Muharram Hasby; Dradjad Irianto; Lucia Diawati (Designs)
Collaborative production is growing in its importance to the global economy, and along with it, so are other collaborative activities along the production chain, such as collaborative design. Nowadays, collaborative detail design can be implemented using Computer-Aided Design (CAD) through task sharing and Product Lifecyle Management (PLM) systems, but collaborative conceptual design is still poorly supported by CAD. Therefore, there is a need for a dedicated CAD platform that can support collaborative conceptual design as well. This paper contains the basic architecture for a CAD system used in collaborative conceptual–embodiment design, the proposed workflow for using the CAD system, and the design comparison method included in the system, that together comprise a CAD-based collaboration framework for conceptual–embodiment design. The framework is based on Coevolution Design Theory and developed such that it can be used to design complex products in an efficient, collaborative manner. A simple case study describing the use of the framework is included to illustrate how the framework can be used to design a product. In the future, this framework can be used to further develop and build a fully functional CAD system that will help designers to engage in a global collaborative setting.